Quasi-maximum likelihood estimation for long memory stock transaction data - under conditional heteroskedasticity framework - A. M. M. Shahiduzzaman Quoreshi; Reaz Uddin; Naushad Mamode Khan (Journal of Risk and Financial Management, 2019)
This paper introduces Quasi-Maximum Likelihood Estimation for Long Memory Stock Transaction Data of unknown underlying distribution. The moments with conditional heteroscedasticity have been discussed. In a Monte Carlo experiment, it was found that the QML estimator performs as well as CLS and FGLS in terms of eliminating serial correlations, but the estimator can be sensitive to start value. Hence, two-stage QML has been suggested. In empirical estimation on two stock transaction data for Ericsson and AstraZeneca, the 2SQML turns out relatively more efficient than CLS and FGLS. The empirical results suggest that both of the series have long memory properties that imply that the impact of macroeconomic news or rumors in one point of time has a persistence impact on future transactions.
Keywords: C13; C22; C25; C51; G12; G14; 330; count data; estimation; finance; high frequency; intraday; time series